PENGARUH RETURN ON EQUITY, CURRENT RATIO, DEBT TO EQUITY RATIO, DAN TOTAL ASSET TURNOVER TERHADAP PRICE TO BOOK VALUE - Siti Zubaedah; Rizki Pratomo Sunarwibowo (MANAJEMEN, 2025)
This study aims to determine the effect of Return on Equity, Current Ratio, Debt to Equity Ratio and Total Asset Turnover on Price to Book Value. The population in this study are companies included in the IDX30 Index on the Indonesia Stock Exchange in the financial statements for the 2018-2022 period. The sampling technique in this study used purposive sampling method and obtained a sample of 11 companies. The analysis technique used is multiple linear regression analysis using Microsoft Excel 2021 Software and SPSS Software version 22.0. The results of this study indicate that Return on Equity, and Total Asset Turnover have a positive and significant effect on Price to Book Value, while Current Ratio and Debt to Equity Ratio have no effect on Price to Book Value.